Prophet Muhammad and His Western Critics - Ibrahim Kalin (International Institute of Islamic Thought, 2001)
This book by the Pakistani scholar Zafar Ali Qureshi is devoted to an important aspect of the relationship between Islam and the West. The image of the Prophet Muhammad (pbu) produced by western scholars of Islam has determined, in many ways, the parameters of the relationship between the two religions and the respective civilizations to which they have given rise. The main argument of Qureshi's extremely well-researched book is that the western scholarship bred by the centuries-old Christian prejudices against Islam has tried to undermine the religious and intellectual basis of Islam by undermining the central place and authority of the Prophet of Islam. This strategy was in no way accidental, because the Christian conception of religion takes as the basis of the Divine revelation not the revealed book, i.e., the Qur'an or the Bible, but Jesus Christ. Seen through the eyes of Christology, Islam could not be anything other than 'Muhammadanism', and any scholarly treatment of it was bound to be based on the figure of the Prophet of Islam. It was within this framework that a number of historicist and materialist accounts were given to prove that the Prophet Muhammad was not an authentic prophet and that his motives were basically political, tribal or economic. The number of books produced in this line of spurious scholarship is immense, and Qureshi has carried out an immense survey of western literature on the life and personality of the Prophet. Although the author spans through hundreds of books produced in the West, he focuses on the work of Rev. Montgomery Watt, the celebrated western scholar of Islam. The reason for this concentration is that Watt's two-volume work on the ...